2016
DOI: 10.1111/jmi.12508
|View full text |Cite
|
Sign up to set email alerts
|

Defining the radiation chemistry during liquid cell electron microscopy to enable visualization of nanomaterial growth and degradation dynamics

Abstract: We present a critical review of methods for defining the chemical environment during liquid cell electron microscopy investigation of electron beam induced nanomaterial growth and degradation. We draw from the radiation chemistry and liquid cell electron microscopy literature to present solution chemistry and electron beam-based methods for selecting the radiolysis products formed and their relative amount during electron irradiation of liquid media in a transmission electron microscope. We outline various met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
231
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(234 citation statements)
references
References 33 publications
3
231
0
Order By: Relevance
“…It is also a consensus that extensive understanding is still needed to quantitatively control the beam effect. More details about current understanding on the electron‐beam effects can be found in another recent review paper …”
Section: Influence and Manipulation Of The Electron Beam In Liquid‐phmentioning
confidence: 99%
“…It is also a consensus that extensive understanding is still needed to quantitatively control the beam effect. More details about current understanding on the electron‐beam effects can be found in another recent review paper …”
Section: Influence and Manipulation Of The Electron Beam In Liquid‐phmentioning
confidence: 99%
“…The majority of the published articles highlight an important challenge in liquid phase TEM, which is to distinguish electron beam induced effects from the phenomena under investigation, and ultimately to suppress these effects. Along with the beam damage already known from TEM imaging in vacuum, liquid phase TEM suffers from additional beam induced effects, the most prominent challenge being the formation of radicals and other reactive species in the liquid upon electron beam irradiation, which significantly changes local chemistry . It was recently found that such a change in chemistry also affects oxides, materials usually considered quite stable under electron beam irradiation .…”
Section: Introductionmentioning
confidence: 99%
“…While this approach allows for direct imaging of nanoscale samples in a thin ( ) liquid layer [4], radiation damage quickly deteriorates the tertiary and quaternary structure of protein aggregates [5,6]. Radiation damage is due mainly to oxidizing radicals created from electron beam induced radiolysis in the liquid layer [7,8]. In this talk, I will outline our recently developed experimental approaches to mitigate radiation damage and enable damage-free imaging of protein aggregate structure and other beam sensitive soft materials.…”
mentioning
confidence: 99%
“…In this talk, I will outline our recently developed experimental approaches to mitigate radiation damage and enable damage-free imaging of protein aggregate structure and other beam sensitive soft materials. These approaches include (1) the addition of radical scavengers [8] to selectively eliminate oxidizing radicals and (2) the use of advanced electron beam control during imaging to reduce the overall production of damaging radicals.…”
mentioning
confidence: 99%